Modern Aspects of Adapting Sustainable Strategic Business Planning. Studies Case from Oil Industry and the Tourism Industry - LINNIK, Andrey; AMERKHANOVA, Altyn; KUDAIBERGENOV, Nuradin; SARIYEVA, Zhanargul; NURLIKHINA, Gulmira (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2021)
Currently, Kazakhstan is an attractive country for attracting foreign investment in the oil and gas sector, since the country's position in the overall ratings of the business environment is generally favorable and growing in comparison with other countries. Taking this into account, the application of strategic planning to oil and gas companies and companies in the tourism sector will be able to successfully counter new global challenges and threats. The specialization of the national economy and the domination of TNCs, the development and growth of entrepreneurship and business as a whole sets in motion flows of managers, representatives of the largest corporations and small private businesses looking for new profitable partnerships, niches to promote their business, increase the capital of a company or a group of people, learning something new for career advancement. The entry of oil companies and companies in the tourism industry to the world market makes the problems of strategic planning of companies especially significant. For the study, fundamental research and applied works of leading domestic and foreign scientists on the formation and development of the business "business" tourism industry and the development of the oil industry were used as a theoretical and methodological basis.